Degradation and sorption of ametryne in two soils with vinasse application - Prata, Fábio; Lavorenti, Arquimedes; Regitano, Jussara Borges; Tornisielo, Valdemar Luís (Pesquisa Agropecuaria Brasileira, 2001)
The aim of this study was to evaluate the effects of vinasse (100 and 200 m3 ha-1) on the degradation and sorption of ametryne in Rhodudalf and Haplorthox soils. For the degradation study an experiment was carried out in a completely randomized design with a factorial experiment of 2 (soils) x 3 (vinasse doses: 0, 100 and 200 m3 ha-1), that was carried by 120 days. The mineralization was evaluated by radiorespirometry. At the end of the incubation (after 120 days), the herbicide was extracted from the soils and detected in the radio-scanner. In parallel, another experiment was carried out in order to evaluate the effect of the vinasse doses and herbicide on the microbial activity, pH and organic carbon content of the soil. The sorption experiment was carried out under the same conditions as the degradation study, with five herbicide concentrations. The ametryne degradation was higher in the presence of 100 m3 ha-1 of vinasse. The vinasse addition increased the microbial activity and the pH. The sorption of ametryne was low and not affected by vinasse.